Epistatic Interactions Between Mutations of Deoxyribonuclease 1-Like 3 and the Inhibitory Fc Gamma Receptor IIB Result in Very Early and Massive Autoantibodies Against Double-Stranded DNA - Weisenburger, Thomas; von Neubeck, Bettina; Schneider, Andrea; Ebert, Nadja; Schreyer, Daniel; Acs, Andreas; Winkler, Thomas H. (Frontiers in Immunology, 2018)
Autoantibodies against double-stranded DNA (anti-dsDNA) are a hallmark of systemic lupus erythematosus (SLE). It is well-documented that anti-dsDNA reactive B lymphocytes are normally controlled by immune self-tolerance mechanisms operating at several levels. The evolution of high levels of IgG anti-dsDNA in SLE is dependent on somatic hypermutation and clonal selection, presumably in germinal centers from non-autoreactive B cells. Twin studies as well as genetic studies in mice indicate a very strong genetic contribution for the development of anti-dsDNA as well as SLE. Only few single gene defects with a monogenic mendelian inheritance have been described so far that are directly responsible for the development of anti-dsDNA and SLE. Recently, among other mutations, rare null-alleles for the Dnase1-like 3 (DNASE1L3) and the Fc gamma receptor IIB (FCGR2B) have been described in SLE patients and genetic mouse models. Here we demonstrate that double Dnase1l3- and FcgR2b-deficient mice in the C57BL/6 background exhibit a very early and massive IgG anti-dsDNA production. Already at 10 weeks of age, autoantibody production in double-deficient mice exceed autoantibody levels of diseased 9-month-old NZB/W mice, a long established multigenic SLE mouse model. In single gene-deficient mice, autoantibody levels were moderately elevated at early age of the mice. Premature autoantibody production was accompanied by a spontaneous hyperactivation of germinal centers, early expansions of T follicular helper cells and elevated plasmablasts in the spleen. Anti-dsDNA hybridomas generated from double-deficient mice show significantly elevated numbers of arginines in the CDR3 regions of the heavy-chain as well as clonal expansions and diversification of B cell clones with moderate numbers of somatic mutations. Our findings show a strong epistatic interaction of two SLE-alleles which prevent early and high-level anti-dsDNA autoantibody production. Both genes apparently synergize to keep in check excessive germinal center reactions evolving into IgG anti-dsDNA antibody producing B cells.